2014
DOI: 10.1038/ncb2930
|View full text |Cite
|
Sign up to set email alerts
|

A time- and matrix-dependent TGFBR3–JUND–KRT5 regulatory circuit in single breast epithelial cells and basal-like premalignancies

Abstract: Basal-like breast carcinoma is characterized by poor prognosis and high intratumor heterogeneity. In an immortalized basal-like breast epithelial cell line, we identified two anti-correlated gene-expression programs that arise among single extracellular matrix (ECM)-attached cells during organotypic 3D culture. The first contains multiple TGFβ-related genes including TGFBR3, whereas the second contains JUND and the basal-like marker, KRT5. TGFBR3 and JUND interconnect through four negative-feedback loops to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 66 publications
2
102
0
Order By: Relevance
“…Interestingly, rpS6 always participates in regulating translation initiation and thus protein synthesis [26], in accordance with GO term analysis (Fig. 5A); on the other hand, rpS6 phosphorylation level regulates several protein signaling pathways involving TGF-β [27,28]accordance with Pathway analysis (Fig. 5D), which suggested that rpS6 probably mediated miR-129-5p induced trastuzumab sensitivity.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 79%
“…Interestingly, rpS6 always participates in regulating translation initiation and thus protein synthesis [26], in accordance with GO term analysis (Fig. 5A); on the other hand, rpS6 phosphorylation level regulates several protein signaling pathways involving TGF-β [27,28]accordance with Pathway analysis (Fig. 5D), which suggested that rpS6 probably mediated miR-129-5p induced trastuzumab sensitivity.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 79%
“…The results are consistent with the concept that the mechanical environment is a vital influence on gene expression. 45,52,53 Our observations indicate that increased understanding of the interactions may signal potential for treatment aimed directly at altering the physical environment or, alternatively, at components of the associated signaling pathways.…”
mentioning
confidence: 84%
“…Immunofluorescence (IF) staining was performed as previously described (46). For ULBP2 and ULBP3 IF staining, the stress ligands were overexpressed with an N-terminal His tag in SupT1 cells.…”
Section: Methodsmentioning
confidence: 99%